Retrobulbar Leiomyosarcoma in a Budgerigar (Melopsittacus undulatus): A Case Report - Eroksuz, Yesari; Canbolat, İbrahim; İncili, Canan Akdeniz; Eröksüz, Hatice (My University, 2025)
This case study documents a rare instance of retrobulbar leiomyosarcoma in a 5-year-old budgerigar. Gross pathological and histological assessments identified a well-circumscribed mass composed of pleomorphic spindle cells encasing the right eyeball. Microscopically, the tumor exhibited tightly interwoven fascicles of spindle-shaped neoplastic cells with elongated, cigar-shaped nuclei, prominent nucleoli, and abundant eosinophilic cytoplasm. The mitotic index was estimated at approximately five mitoses per high-power field, indicating moderate proliferative activity. Immunohistochemical analysis revealed strong cytoplasmic positivity for vimentin and smooth muscle actin, while staining for desmin was negative, supporting a smooth muscle origin. These findings underscore the importance of integrating histomorphological characteristics with immunohistochemical profiling for the accurate diagnosis of orbital leiomyosarcoma, particularly in distinguishing it from other spindle cell tumors in the periocular region. This case emphasizes the need to consider poorly differentiated leiomyosarcoma in the differential diagnosis of avian orbital neoplasms.
Keywords: Immunohistochemistry; Avian; histopathology; Budgerigar; retrobulbar leimyosarcoma